THE STRATEGIES OF TARGETING CONSUMER BUYING DECISION IN PALMART MINIMARKET, PONTIANAK - fahmi, Zul; Octaviani, Dina (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2018)
Retail business that is now very popular is a business that supports many people and gives many benefits to some people. Minimarket, which has long been known to the people of Pontianak, is a form of retail business that is very rapidly growing and its existence is very beneficial to the community. For that, producers need strategies with the objective of achieving competitive advantage and need information about factors that influence consumer behavior in making decisions regarding the purchase of products. The purpose of this study is to find out how the strategy of targeting consumer buying decisions in Palmart Minimarket, Pontianak. This type of research is survey research and data collection techniques used was questionnaire, while the respondents were consumers who had shopped in Palmart Minimarket Pontianak, the data analysis technique used was the Factor Analysis method with Accurate Use correlation/correlation matrix between variables using Bartlett Test of Sphericity or Measure of Sampling Adequacy (MSA). The value of KMO/MSA ranges from 0 - 1 with the criteria used for interpretation. The expected target in this study was to inform how the right strategy of Targeting Consumer Buying Decisions in the Palmart Minimarket, Pontianak. The output of this research is teaching material, paper for national scientific seminars, and publications in national-accredited scientific journals.